A Current Status of the Moral Learning Situation of Thai Youths in the Post Modernized World through a Secular Humanistic Lens - Pienlamlert, Nichakarn; Hongwityakorn, Ubonwan (Journal of Graduate MCU KhonKaen Campus, 2024)
This research aims to study the current status of the moral learning situation and the moral learning process of Thai youths in the post-modernized world through a secular humanistic approach. The research uses mixed-method Research methodology both quantitatively and qualitatively. The sample size is simple random sampled at 575 comprising of Thai Youths in the post-modernized world aged 15-18. The research methods include documentary research through relevant documents, literature concepts, theories, previous researches on the topics, online research repositories and websites, quantitative questionnaire using 5-point Likert scale which receives 0.90 score on the Index of item of Objective Congruence (IOC) passing the Reliability receiving 0.97 score on Cronback’s alpha reliability test. The researcher compares and contrasts the research result with the narrative analysis from the in-depth interview with 12 purposively selected Youth subjects, aged between 15-18 and 9 stakeholders in the moral learning process of Thai Youths in the post-modernized world. Though the quantitative research result shows no statistical significance between demographic attributes, i.e., gender, age, academic status, family status, and parent’s occupation and the moral learning development of Thai Youths, the interview results reveals significant contrast with the quantitative result as the 12 subjects expressed similar opinions, concerns and comments that the demographic attributes play a significant role according to the 4 aspects of Bronfenbrenner’s Bioecological Model, i.e., Process-People-Context-Time (PPCT)